Program Pengenalan Arab Pegon Pada Usia Dini di TPQ Kanzul ‘Ulum Pogar Tunglur Badas - Mohammad Adi Prasetiyo; Wildan Habibi (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2020)
Children are the next generation of nations and religions. Many of their parents want their children to continue their education to boarding schools. Because in the eyes of the wider community education in pesantren is guaranteed if the problem is about religion. In addition, life in boarding schools can also prevent them from falling into an environment that is not expected. The research approach used in this research is the PAR method or Participatory Action Research. With the Research program, "Introduction of Arab Pegon at an Early Age in Tpq Kanzul 'Ulum" on August 3, 2020 in Pogar Hamlet, Tunglur Village Badas District brought a little significant change, especially in the environment of Tpq Kanzul 'Ulum. This, researchers say based on some data that researchers obtained after this program researchers carried out. Santriwan who had never previously known about Pegon Arabic became familiar about arab pegon can even read and write with arab pegon.